The Social Planning Problem with Costly Information Processing: Towards Understanding Production Decisions in~Centralized Economies - Dominik Naeher (Economica, 2022)
It has long been argued that market economies feature an inherent advantage over centralized economies because they are subject to fewer information processing needs. However, very little work has investigated the role of these needs in explaining differences in optimal production decisions between centralized and market economies. This paper uses a rational inattention approach to study the decision problem of a social planner who faces uncertainty about households' preferences and can reduce this uncertainty by allocating scarce resources to processing information. The model shows that costly information processing has important implications for optimal production decisions, including for the trade-off between consumption and leisure, the optimal range of different goods produced, and the role of correlated consumer preferences. Overall, the results suggest that differences in empirical production decisions between socialist and capitalist countries may be driven by the different information needs and associated costs of processing information inherent to each economic system, rather than by differences in ideology or political preferences.
Keywords: 330